Gas adsorption capacity of metal oxide modified zeolite adsorbents - Chieng, Yu Yuan; Kamarudin, Khairul Sozana Nor; Hamdan, Halimaton; Mat, Hanapi (Universiti Teknologi Petronas, 2004)
Advance developments in preparation, characterization and modification of zeolites and processes have leading to new insights in adsorbent property and performances. This research studies the modification of zeolite physicochemical properties and its gases (N2, O2 and CH4) adsorptive characteristics by incorporating metal oxides into the zeolitic system using thermal monolayer dispersion method. The structures of the metal oxide modified zeolites were characterized by powder XRD; the physical features and gas adsorption capacity were analyzed using TGA and Quantachrome NOVA 1000. Results revealed that types of metal oxides, calcination temperature, metal oxide loading, concentration and the modification techniques greatly affect the modified zeolite adsorbents structural properties and its gases adsorption capacity.